A Narrative Analysis of the Lived Experiences of Nontraditional Black Female Students Who Attend an Historically Black College or University - McBride, Meghan Rose (My University, 2018)
This study employed narrative analysis within the theoretical frameworks of critical race feminism (CRF) and Black feminist thought (BFT) to explore the lived experiences of six Black female nontraditional students at an Historically Black University (HBCU). Data collected in this study came primarily from interviews with the participants but included observations and document analysis as well. Using connecting and categorizing strategies to organize the data into a priori and inductively generated themes resulted in a collective narrative that told the story of six Black reentry women. The presentation of data maintained the fidelity of the guiding theoretical frameworks by privileging the women’s voices and allowing the stories of their lived experiences to serve as counter-narratives that resist persistent negative stereotypes of Black women in America. Findings from this study indicate that the Black reentry women who participated are committed to their education and determined to graduate but have had to navigate innumerable personal and institutional barriers to be successful in college. These women are most comfortable when in the classroom with others like them and indicate a lack of campus life programs in which they fit. Because the women are eager to enter their chosen career field, they appreciate rigor in curriculum and instruction, but believe the institution lacks the systems to appropriately support that rigor. Finally, the women have high expectations for immediacy and professionalism, but feel that the institution has overwhelmingly underdelivered. The implications for the institution are grim. When students leave the school with a lack of value in the institution, they are less likely to recruit others to the school or provide financial support as alumni. Several recommendations are provided to remedy these situations.
CHAPTER I: INTRODUCTION 1 -- Background of Study 1 -- Statement of the Problem 3 -- Significance of Study 11 -- Research Questions 14 -- Conceptual Framework 15 -- Research Goals 21 -- CHAPTER II: LITERATURE REVIEW 24 -- Enrolling and Persisting in College 26 -- Challenges as Students 30 -- Within-Group Differences 34 -- Cultural Responsiveness 37 -- Summary 40 -- CHAPTER III: RESEARCH DESIGN 42 -- Setting 44 -- Participants 45 -- Data Collection 46 -- Data Analysis 48 -- Presentation of Data 53 -- Reliability and Validity 56 -- CHAPTER IV: AN EXAMINATION OF PARTICIPANTS’ LIFE HISTORIES AND THE EXPERIENCES AND VALUES THAT INFLUENCED THEM TO REENTER COLLEGE AT AN HBCU 62 -- Brief Life Histories 63 -- Amber 63 -- Debbie 65 -- Kayla 75 -- Shaquita 79 -- Shontae 84 -- Zoe 87 -- Experiences that Delayed Participants’ Traditional Matriculation into College 94 -- Hardships 94 -- Amber 95 -- Shontae 105 -- Zoe 107 -- Analysis 109 -- Marginalization and Barriers to Reentry 110 -- Amber 112 -- Debbie 112 -- Zoe 113 -- Analysis 113 -- The Decision to Reenter College 114 -- Experiences 115 -- Outside Encouragement 116 -- Debbie 116 -- Kayla 117 -- Analysis 118 -- Coping with Challenges 118 -- Kayla 119 -- Zoe 120 -- Analysis 120 -- Life’s Critical Moments 120 -- Debbie 121 -- Shaquita 121 -- Shontae 124 -- Analysis 128 -- Values 129 -- Being a Role Model 129 -- Debbie 130 -- Shontae 130 -- Analysis 131 -- Having a Career 132 -- Zoe 132 -- Analysis 133 -- Having an Education 133 -- Debbie 133 -- Analysis 134 -- The Decision to Attend the HBCU 134 -- Family Connection 135 -- Amber 135 -- Debbie 136 -- Kayla 137 -- Analysis 137 -- Convenience 137 -- Shaquita 138 -- Shontae 138 -- Analysis 138 -- The Passion behind Selecting a Major 139 -- Amber 140 -- Kayla 141 -- Shontae 141 -- Zoe 141 -- Analysis 143 -- Conclusions 144 -- CHAPTER V: AN EXAMINATION OF PARTICIPANTS’ EXPERIENCES IN COLLEGE 147 -- Overcoming Challenges 147 -- Institutional Barriers 148 -- Debbie 149 -- Kayla 149 -- Shaquita 151 -- Shontae 152 -- Zoe 155 -- Analysis 156 -- Interrole Conflict 157 -- Amber 158 -- Kayla 159 -- Shontae 162 -- Zoe 168 -- Analysis 170 -- Finding their Place within the Campus Culture 171 -- Helping Each Other 172 -- Amber 172 -- Debbie 173 -- Shontae 174 -- Analysis 175 -- Mentoring/Maternal Relationship 175 -- Amber 176 -- Debbie 177 -- Kayla 178 -- Analysis 179 -- Comfort Level on Campus 179 -- Amber 180 -- Debbie 181 -- Shaquita 183 -- Shontae 183 -- Zoe 184 -- Analysis 185 -- The Women as Students 186 -- Amber 186 -- Debbie 187 -- Shaquita 190 -- Shontae 192 -- Zoe 195 -- Analysis 197 -- Perspectives on the Institution 199 -- Instructors and the Curriculum 199 -- Amber 200 -- Debbie 201 -- Kayla 205 -- Shaquita 207 -- Shontae 208 -- Zoe 210 -- Analysis 211 -- Overall Experience 212 -- Debbie 212 -- Kayla 215 -- Shaquita 216 -- Shontae 218 -- Zoe 219 -- Analysis 221 -- Persistence 221 -- Non-Institutional Factors Supporting Persistence 222 -- Debbie 222 -- Kayla 223 -- Shontae 224 -- Zoe 225 -- Analysis 225 -- Institutional Factors Supporting Persistence 226 -- Amber 226 -- Debbie 227 -- Shontae 230 -- Zoe 233 -- Analysis 235 -- Conclusions 236 -- CHAPTER VI: DISCUSSION 238 -- Summary of the Study 238 -- Conclusions from a Critical Race and Black Feminist Perspective 240 -- Limitations of the Study 242 -- Implications of the Study 243 -- Nontraditional learning communities 247 -- Targeted Academic Support Services 249 -- Consideration of and Support for the Whole Self 251 -- Recommendations for Future Research 253 -- Conclusion 254 -- EPILOGUE 259 -- REFERENCES 261 -- APPENDIX A: Interview 1 Protocol – Life History 269 -- APPENDIX B: Interview 2 Protocol – Matriculation Experiences 271 -- APPENDIX C: Interview 3 Protocol – Meaning-Making 273 -- APPENDIX D: Valdosta State University IRB Application 275 -- APPENDIX E: Valdosta State University IRB Exemption Report 284 -- APPENDIX F: [Dabny] State University IRB Exemption Report 286 -- APPENDIX G: Email Invitation to Potential Participants 288 -- APPENDIX H: Sample Data Analysis – Construction of the Life History Vignette 290 -- APPENDIX I: Participant Comparison Chart 293 -- APPENDIX J: Coding Matrix 295 -- APPENDIX K: Code System 297.
Keywords: Dissertations, Academic--United States; Nontraditional college students; African American universities and colleges; African American women college students; Discourse analysis, Narrative; Returned students